2011
DOI: 10.1002/qua.22657
|View full text |Cite
|
Sign up to set email alerts
|

A 2D spinless version of Dirac's equation written in a noninertial frame of reference

Abstract: ABSTRACT:In this article, we present a quantized classical-like wave equation. It is obtained by considering the equivalence between the Hamilton-Jacobi eq. (which belongs to the usual manifold R 3 R of General Relativity), with our two spinor versions of the Dirac eq. (which belongs to the associated complex manifold C C). In which the electron is considered as a particle-like entity, instead of the usual wave-like interpretation of standard Quantum Mechanics. We also consider the transformation properties be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Now, the homogeneous system of equations in the coefficients 00 k a corresponding to the determinant Eq. (15) has a kernel generated by the eigenvalue 1  , whose base is given by the two linearly independent column vectors   12 (20)…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the homogeneous system of equations in the coefficients 00 k a corresponding to the determinant Eq. (15) has a kernel generated by the eigenvalue 1  , whose base is given by the two linearly independent column vectors   12 (20)…”
Section: Theorymentioning
confidence: 99%
“…In a previous work [1] we have shown that, by taken into account the classical conservation theorems before the Dirac matrices are found, it is possible to use 2x2 matrices instead the usual 4x4 matrices in the solution of the hydrogen atom, which yields a considerable reduction in the complexity of the problem. In this work, we try to get the same reduction in the dimensions of the Dirac matrices for the problem of the helium atom, which allows us to use 4x4 matrices instead of the 16x16 matrices of the Breit theory of the helium [2,3], which in spite of this is our starting point.…”
Section: Introductionmentioning
confidence: 99%
“…From this non-linear momentum variation equation for a non-conservative system, which is analogous to (2) for a conservative system, the electron trajectories resulting in the stable attractor mentioned above will be obtained. Thus, Equation (11) is the linear differential equation associated with the non-linear momentum equation, (14).…”
Section: E Lmentioning
confidence: 99%
“…We can now perform the reduction of both the equations of motion, (11) and (14). Starting with the former, we consider a variation in path with a constant angular momentum 3 0 L   , so that .…”
Section: Determination Of the Electron Path Functions In The Formatiomentioning
confidence: 99%
See 1 more Smart Citation